INVESTIGATING READING COMPREHENSION PROBLEMS IN ENGLISH LANGUAGE LEARNING - Ai Karmini; M Anjar Nugraha; Dody Wahyudi Purnama (Bajang Institute, 2026)
This study investigated the reading comprehension problems experienced by sixth-grade students in English language learning at SD Negeri Sanggarwinaya. The research was conducted because many students had difficulty understanding English texts, particularly in identifying main ideas, distinguishing supporting details, understanding vocabulary, and making inferences. The objective of the study was to identify the problems faced by students and the factors influencing their reading comprehension ability. This research employed a qualitative case study design. The participants consisted of ten sixth-grade students and one English teacher. Data were collected through classroom observation, interviews, documentation, and a reflective journal, then analyzed through data reduction, data presentation, and conclusion drawing. The findings showed that students experienced significant difficulties in understanding unfamiliar vocabulary, identifying the main idea of a paragraph, and comprehending the overall meaning of a text. In addition, students tended to read word by word and rarely applied reading strategies such as skimming and scanning. The study also found that low motivation, limited vocabulary exposure, inadequate family support, and teacher-centered instructional practices contributed to students’ reading comprehension problems. Therefore, improving reading strategies, motivation, and instructional support is necessary to enhance students’ English reading comprehension